2021
DOI: 10.3389/fncir.2021.688234
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocinergic Feedback Circuitries: An Anatomical Basis for Neuromodulation of Social Behaviors

Abstract: Oxytocin (OT) is a neuropeptide produced by hypothalamic neurons and is known to modulate social behavior among other functions. Several experiments have shown that OT modulates neuronal activity in many brain areas, including sensory cortices. OT neurons thus project axons to various cortical and subcortical structures and activate neuronal subpopulations to increase the signal-to-noise ratio, and in turn, increases the saliency of social stimuli. Less is known about the origin of inputs to OT neurons, but re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 70 publications
2
9
0
Order By: Relevance
“…Our data showed that PVH Oxt neurons mediated appetite suppression signals. Previous studies have shown that both oxytocinergic neurites and Oxtr -expressing neurons can be found in various brain and spinal cord regions ( Jurek and Neumann, 2018 ; Lefevre et al, 2021 ; Newmaster et al, 2020 ; Oti et al, 2021 ; Zhang et al, 2021 ). In the present study, by AAV-Cre -mediated cKO, we found that Oxtr expressed by neurons in the posterior hypothalamic regions, especially those in the ARH, mediates appetite suppression signals ( Figures 5 and 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that PVH Oxt neurons mediated appetite suppression signals. Previous studies have shown that both oxytocinergic neurites and Oxtr -expressing neurons can be found in various brain and spinal cord regions ( Jurek and Neumann, 2018 ; Lefevre et al, 2021 ; Newmaster et al, 2020 ; Oti et al, 2021 ; Zhang et al, 2021 ). In the present study, by AAV-Cre -mediated cKO, we found that Oxtr expressed by neurons in the posterior hypothalamic regions, especially those in the ARH, mediates appetite suppression signals ( Figures 5 and 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that PVH OT neurons mediated appetite-suppression signals. Previous studies have shown that both oxytocinergic neurites and OTR-expressing neurons can be found in various brain and spinal cord regions (Jurek and Neumann, 2018; Lefevre et al, 2021; Newmaster et al, 2020; Oti et al, 2021; Zhang et al, 2021). In the present study, by AAV-Cre mediated cKO, we found that OTR expressed by neurons in the posterior hypothalamic regions, especially those in the ARH, mediates appetite-suppression signals (Figure 5 and 6).…”
Section: Discussionmentioning
confidence: 99%
“…This review will specifically highlight interactions between oxytocin and opioidergic circuits [82]. Existing reviews have done an excellent job summarizing known behavioural effects of oxytocin [43,48,50,52,58,71,82,83], the neural mechanisms underlying these effects [15][16][17]84,85] and potential hypotheses about the role of oxytocin in the brain and social behaviour [20,22,24]. We will not attempt to duplicate those here.…”
Section: Introductionmentioning
confidence: 99%